EVALUATION OF THE PROGRESSION OF AXIAL SPONDYLOARTHRITIS IN THE EARLY STAGES OF THE DISEASE IN REAL CLINICAL PRACTICE: THE POSSIBILITIES OF USING THE SUMMARY SCORE OF RADIOGRAPHIC SACROILIITIS - Sh. F. Erdes; D. G. Rumyantseva; A. V. Smirnov (Научно-практическая ревматология)
The currently used methods for evaluating the progression of structural damages in early axial spondyloarthritis (axSpA) are little suitable to real practice since they require specially trained radiologists and increase a patient's exposure to radiation due to the need for radiography of three regions of the axial skeleton. In addition, the first radiological bone changes in the sacroiliac joints (SIJ) appear only many years after the onset of the disease, the overlying spine areas are involved in the pathological process. Objective: to develop a method for evaluating the radiographic progression of sacroiliitis (SI) in early axSpA for real clinical practice. Subjects and methods. The investigation enrolled patients from the early spondyloarthritis cohort (ESAC) formed at the V.A. Nasonova Research Institute of Rheumatology. The current ESAC comprised 164 patients; the analysis included 68 patients who had been followed up for at least 2 years and had plain pelvic bone films at the inclusion in the cohort and at 2-year follow-up. To evaluate disease progression, the investigators used the sum of radiographic SI stages in the left and right SIJs (the summary stage of radiographic SI (ssrSI), which was calculated at baseline and at 2-year follow-up. A formula for determining the rate of radiographic progression was derived. Results and discussion. At baseline and at 2-year follow-up, the median ssrSI difference (ΔssrSI) in 68 patients was 0 [0; 1.0]. During the study period, almost 60% of the patients had no progression of ssrSI, i.e. ΔssrSI was 0 in these patients, 1 and 2 scores in 12 (18%) and 13 (19%) patients, respectively, and there were singly cases, in which this figure was equal to 3, 4 and 7. The mean value of ssrSI was 3.5±1.6 at baseline and increased by 0.8, reaching 4.3±1.5 at 2 years (p = 0.006). Before included into the investigation, the patients had a progression rate of 1.75 during 1 year, which decreased to 0.4 per year in the active follow-up period. At the time of inclusion in the study, 40 (58.8%) of the 68 patients had ankylosing spondylitis (AS), and at 2 years their number increased to 51 (75.0%); i.e. 11 (39%) patients were observed to have progression of non-radiographic axSpA to AS. Conclusion. The proposed procedure to calculate ssrSI is easily feasible in real practice; it fails to lead to additional radiation exposure, is economically feasible, and allows one to monitor the rate of progression of axSpA in the early stage of the disease.